Please help. Been staring at it for a few hours now.

cosysin2xdx +(cos^2y - cos^2x)dy = 0

February 13, 2018 - 1:44pm

#1
AthenaKyuwa

Differential Equation

Please help. Been staring at it for a few hours now.

cosysin2xdx +(cos^2y - cos^2x)dy = 0

- strength of materials
- Analytic Geometry Problem Set [Locked: Multiple Questions]
- Equation of circle tangent to two lines and passing through a point
- Product of Areas of Three Dissimilar Right Triangles
- Perimeter of Right Triangle by Tangents
- Differential equations
- Laplace
- Families of Curves: family of circles with center on the line y= -x and passing through the origin
- Family of Plane Curves
- Differential equation

Home • Forums • Blogs • Glossary • Recent

About • Contact us • Disclaimer • Privacy Policy • Hosted by WebFaction • Powered by Drupal

About • Contact us • Disclaimer • Privacy Policy • Hosted by WebFaction • Powered by Drupal

Forum posts (unless otherwise specified) licensed under a Creative Commons Licence.

All trademarks and copyrights on this page are owned by their respective owners. Forum posts are owned by the individual posters.

All trademarks and copyrights on this page are owned by their respective owners. Forum posts are owned by the individual posters.

The equation is not exact, but can be made so by using a special integrating factor. If we write it as:

$$M(x,y) dx + N(x,y) dy=0$$

then...

$$\frac{dM}{dy} = -\sin (y) \sin (2x)$$

and...

$$\frac{dN}{dx}= -2(-\sin (x) \cos (x)) = \sin (2x)$$

So

$$\frac{N_x - M_y}{M} = \frac{1+\sin (y)}{\cos (y)}$$

which depends on $y$ alone. Setting $u(y) = e^{\int \frac{N_x - M_y}{M} dy}$ gives

$$u(y) = \frac{1+\sin (y)}{\cos^2(y)}$$

where we used some trigonometric identities to get this convenient form.

Multiplying through by $u(y)$ gives:

$$u(y)M(x,y) dx + u(y)N(x,y) dy = 0$$

If we call $u(y)M(x,y) = F(x,y)$ and $u(y)N(x,y)=G(x,y)$, then...

$$\frac{dF}{dy} =\frac{\sin (2x) +\sin (2x) \sin (y)}{\cos^2 (y)} = \frac{dG}{dx}$$

and the new equation is exact. So, there exists a function $f(x,y)$ such that...

$\frac{df}{dx} = F$ and $\frac{df}{dy} = G$ and all solutions are of the form

$$f(x,y)=C$$

Now...

$$f(x,y) = \int F(x,y) dx = -\cos^2(x) \frac{1+\sin(y)}{\cos(y)} +g(y)$$

where $g(y)$ is a constant of integration. Taking the partial of this with respect to $y$ and comparing it to $G(x,y)$ (which must also be the partial of $f$ with respect to $y$) gives...

$$-\cos^2(x) \frac{1+sin(y)}{cos^2(y)} +g ' (y) = 1+\sin(y) -\cos^2(x) \frac{1+sin(y)}{cos^2(y)}$$

so that $g ' (y) = 1+\sin(y)$. It follows that

$$g(y) = y-\cos(y)$$

We omit the constant of integration because we'll set our solution $f$ to a constant. Then

$$f(x,y) = y-\cos (y) - \cos^2 (x) \frac{1+\sin (y)}{\cos (y)}$$

and all solutions are defined implicitly by

$$\color{green}{y-\cos (y) - \cos^2(x) \frac{1+\sin(y)}{\cos(y)} = C}$$

If you prefer, you can multiply through by $\cos (y)$ and write the solutions as

$$\color{green}{y \cos (y) - \cos^2 (y) - (1+sin(y)) cos^2(x) - C cos(y) = 0} $$

Alternate solutions are encouraged....